Modifikasi Kue Sohun Putu Mayang dengan Angkak untuk Meningkatkan Nilai Fungsional pada Pangan Tradisional - Estrella, Vanessa Luz; Muhammad Irfan; Rendy David Sanjaya (Journal of Micro, Small and Medium Enterprises, 2025)
This research aims to develop an innovative modification of traditional Indonesian food, Putu Mayang, by utilizing sohun (mung bean starch noodles) and angkak (red fermented rice) as a natural colorant with added health benefits. Putu Mayang is traditionally made from rice flour and synthetic coloring, but this study replaces the base with sohun to create a gluten-free alternative, while incorporating angkak to enhance its nutritional value and sensory appeal. Using a qualitative approach combined with literature review and simple experimental testing, this study assesses the product’s nutritional composition, organoleptic qualities (taste, texture, aroma, and color), and potential health impacts. The results showed that angkak contributes a distinctive natural red hue and imparts a warm, pleasant aroma to the cake. Nutritionally, the product contains complex carbohydrates, plant-based fats, fiber, antioxidants, and monacolin K, which is known to help lower LDL cholesterol and improve cardiovascular health. Organoleptic tests revealed positive responses, especially in terms of texture (soft and chewy) and taste (sweet and savory balance). However, limitations include color stability over time and the relatively higher cost of natural ingredients. This innovation presents a promising alternative to traditional snacks by combining culinary heritage with functional health benefits. The angkak-based Sohun Putu Mayang is suitable for consumption across generations, providing both cultural value and nutritional enrichment in a single dish